Modified Peroral Endoscopic Myotomy Technique for Type II Achalasia: A Multicenter Retrospective Study - Huahui Zhang; Kuangjing Wang; Ying Fang; Zhe Xiong; Min Lin; Lifeng Jiang; Qiuya Niu; Jin Huang (Gastroenterology Research and Practice)
Aim. This retrospective study is aimed at evaluating the outcomes of a modified peroral endoscopic myotomy (POEM) technique in patients with type II achalasia. Methods. We performed a modified POEM procedure, which involved a shorter (total myotomy length=4 cm), full-thickness myotomy, on 31 patients with type II achalasia. Clinical success rates, technical success rates, pre- and postoperative esophageal manometry results, complications, and reflux-related adverse events were evaluated. Results. The clinical success (Eckardt score≤3) rates were 100% and 88.9% within 2 years and beyond 2 years postoperatively, respectively. The median lower esophageal sphincter pressures (LESP) decreased from 31.6 (26.7-49.7) mmHg preoperatively to 13.4 (10.5-21.6) and 11.8 (7.4-16.7) mmHg (P<0.001) at 6 and 12 months postoperatively, respectively. The median integrated relaxation pressure (IRP) decreased from 27.8 (20.6-37.5) mmHg preoperatively to 12.9 (11.3-23.4) and 11.6 (9.6-16.8) mmHg (P<0.001) at 6 and 12 months after POEM, respectively. Only one case (3.2%) of mucosal injury, four (12.9%) cases of reflux esophagitis, and two (6.5%) cases of gastroesophageal reflux symptoms were reported. Conclusions. The modified POEM technique showed excellent outcomes in patients with type II achalasia.